Pengaruh Suku Bunga, Inflasi, Dan Harga Minyak Dunia Terhadap Harga Saham Dengan Risiko Sistematis Sebagai Variabel Intervening (Studi Pada Perusahaan Sub Sektor Logam Dan Sejenisnya Yang Terdaftar Di Bursa Efek Indonesia Periode 2016 – 2021) - Apin Apiun; Wawan Ichwanudin; Ana Susi Mulyani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The performance of a company can be seen from the company's stock price. The stock price shows how far the company can prosper shareholders. Fluctuating stock prices are influenced by various factors. External factors include macroeconomics and market conditions themselves. Interest rates, inflation, and oil prices are examples of many macroeconomic factors that are considered to have an impact on stock prices. This study aims to determine whether there is an influence between interest rates, inflation, and world oil prices on stock prices, using systematic risk as an intervening variable. The type of research used is descriptive and associative research. The research population is manufacturing companies in the metal sub- sector and the like listed on the IDX for the 2016-2021 period as many as 14 companies. The data used is secondary data. Data analysis using descriptive statistics, and path analysis and partial tests (t-tests) using version 10 of the Eviews program. The results of structural regression 1 (one) show that variable interest rates, inflation, and oil prices have a significant positive effect on systematic risk. The results of structural regression 2 (two) show that variable interest rates, oil prices, and systematic risk have a significant negative effect on stock prices while inflation variables have a negative effect insignificant. The results of the track analysis and sobel test show that systematic risk is able to mediate the influence of interest rates, inflation, and oil prices on stock prices. As a result, when interest rates, inflation, and world oil prices increase, higher market risks will reduce stock prices. Keywords: Interest Rate, Inflation, Oil Price, Systematic Risk, Stock Price